Working Memory Load Effects on the Tilt Aftereffect - Mei, Gaoxing; Cen, Mofen; Luo, Xu; Qiu, Shiming; Pan, Yun (Frontiers in Psychology, 2021)
Prolonged exposure to an oriented stimulus causes a subsequent test stimulus to be perceived as tilted in the opposite direction, a phenomenon referred to as the tilt aftereffect (TAE). Previous studies have demonstrated that high-level cognitive functions such as attention can modulate the TAE, which is generally well-known as a low-level perceptual process. However, it is unclear whether working memory load, another high-level cognitive function, could modulate the TAE. To address this issue, here we developed a new paradigm by combining a working memory load task with a TAE task. Participants firstly remembered a stream of digits (Experiment 1) or four color-shape conjunctions (Experiment 2) under high/low load conditions, and then recognized the probe stimuli (digits or a color-shape conjunction), which were presented at the center of an adapting grating. After the recognition task (i.e., the adaptation stage), participants performed an orientation judgment task to measure their TAEs. The result of Experiment 1, where the load stimuli were digits, showed that the magnitude of the TAEs were reduced under the condition of the high working memory load compared to that of the low working memory load. However, we failed to replicate the finding in Experiment 2, where the load stimuli were color-shape conjunctions. Together, our two experiments provided mixed evidence regarding the working memory load effects on the TAE and further replications are needed in future work.